"Espichamento", poisoning of cattle by Solanum malacoxylon, in the pantanal region of Mato Grosso, Brazil. II. Complementary studies - Tokarnia, Carlos Hubinger; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
Solanum malacoxylon Sendtner was found in all the western pantanal, a temporarily flooded lowland region of Mato Grosso, where the soils are clayish. In the eastern pantanal, mainly of sandy soils, the plant almost does not occur. The presence of S. malacoxylon coincides with the occurrence of "espichamento" disease and vice-versa. Besides S. malacoxylon with glabrous leaves, a puberulous form, S. malacoxylon var. brachychaeta, was found in the pantanal region, which has the same toxic properties as the glabrous form. Bovines in the process of recovering from the natural disease, simply by their removal from areas where S. malacoxylon occurs, were studied. It was seen that the calcium deposits in the different organs had diminished, indicating decalcification, but that the other connective tissue changes were still present. The disease could be experimentally produced in 1 to 2 year old bovines with amounts smaller than given previously, as low as 0.04 g/kg per week of the dried leaves. A single dose of 10 g/kg caused changes of the same nature as were observed in animals that received similar quantities of the plant, but subdivided into smaller doses over several weeks; the lesions in the cardio-vascular system were almost as pronounced, whereas in the lungs they were much less severe. Experiments performed in a calf with the plant collected two years previously and kept at room temperature, showed that its toxicity was unaltered.